The influence of celebrity endorsement, word of mouth, and quality of information on the decision to use facial skincare service - Yuli Asbar; Sapna Biby; Maryudi; Duwi Permata (Universitas Negeri Padang, 2021)
This study aims to analyze the influence of celebrity endorsement, word of mouth, and quality of information on the use of facial skincare services (Study on skincare Sheen in Lhokseumwe City). The data analysis method used is multiple linear regression analysis and classical assumption test. The number of respondents used in the study was 96 respondents. Partially the results of the study stated that the variables of celebrity endorsement, word of mouth, and the quality of information had a positive and significant effect on the decision to use facial skincare services on Lhokseumawe City. Simultaneously the results of the study stated that the variables celebrity endorsement, word of mouth, and quality of information had a positive and significant effect on the decision on the use of facial skincare services on skincare Sheen in Lhokseumawe.